Laughter and ridicule : towards a social critique of humour - Billig, Michael (Theory, culture & society (Unnumbered), 2005)
F̀rom Thomas Hobbes' fear of the power of laughter to the compulsory, packaged "fun" of the contemporary mass media, Billig takes the reader on a stimulating tour of the strange world of humour. Both a significant work of scholarship and a novel contribution to the understanding of the humourous, this is a seriously engaging book' - David Inglis, University of Aberdeen. This delightful book tackles the prevailing assumption that laughter and humour are inherently good. In developing a critique of humour the author proposes a social theory that places humour - in the form of ridicule.